Candidate targets for Multilocus Sequence Typing of Trypanosoma cruzi: Validation using parasite stocks from the Chaco Region and a set of reference strains - Lauthier, Juan José (2012)
A Multilocus Sequence Typing (MLST) scheme was designed and applied to a set of 20 Trypanosoma cruzi stocks belonging to three main discrete typing units (T. cruzi I, V and VI) from a geographically restricted Chagas disease endemic area in Argentina, 12 reference strains comprising two from each of the six main discrete typing units of the parasite (T. cruzi I-VI), and one T. cruzi marinkellei strain. DNA fragments (≅400-bp) from 10 housekeeping genes were sequenced. A total of 4178. bp were analyzed for each stock. In all, 154 polymorphic sites were identified. Ninety-five sites were heterozygous in at least one analyzed stock. Seventeen diploid sequence types were identified from 32 studied T. cruzi stocks (including the reference strains). All stocks were correctly assigned to their corresponding discrete typing units. We propose this MLST scheme as provisional, with scope for improvement by studying new gene targets on a more diverse sample of stocks, in order to define an optimized MLST scheme for T. cruzi. This approach is an excellent candidate to become the gold standard for T. cruzi genetic typing. We suggest that MLST will have a strong impact on molecular epidemiological studies of Chagas disease and the phylogenetics of its causative agent.